DEVELOPMENT OF MUSIC FESTIVALS IN LATGALE - Gusāns, Ingars (Via Latgalica, 2013)
The topic of this article is to illustrate the contribution of festivals to Latgalian culture. The article gives an overview on the development of the festivals: Latgales Televīzijas Mūzikas festivāls, ”Osvalds”, ”Muzykys Skrytuļs” and Latgales Mūzikas festivāls. The article is based on interviews with the festival organizers, available press materials, internet resources and the author’s personal observations both as a listener and a participant of the described festivals. Festivals are mentioned in chronological order. Latgales Televīzijas Mūzikas festivāls was the festival that started advertising of regional art in Latvia. It was characterized by a variety of genres and the opportunity for artists to introduce themselves to the general public on a high professional level. “Osvalds” is an entertainment festival for people of different taste. It popularizes regional associations and most up-to-date Latvian artists; the Latgalian element does occur, but it is not the main objective. “Muzykys Skrytuļs” has promoted the creation of Latgalian songs, the foundation of music groups and has given opportunity for newcomers to perform on a bigger stage. By concert records and live broadcasts this festival makes a great contribution to the development and the popularization of Latgalian identity. Latgales Mūzikas festivāls has provided an opportunity to the most famous, up- to-date Latgalian artists to perform at the festival on the main stage, thus filling a time gap within the field of Latgalian festivals. Each festival expresses the Latgalian identity in a different manner. However it can be perceived in each of them, therefore it is possible to affirm that festivals integrate, help to maintain and console the Latgalian identity. Most prominently it demonstrates to the new generation that Latgalians are a part of the modern world just like everyone else and that in order to express their cultural identity they themselves could actively participate in various folklore and folk dance groups or even start a rock band that performs in Latgalian language.